Efforts to Improve the Quality of Shrimp Pasted Products through the Implementation of the Plan-Do-Check-Act Cycle and the Root Cause Analysis Method at UD Nurhayati - Nando, Fiky Two; Avnanta Puteri, Agatha Hannabel; Qinthara, Bahij Naufal; Fernandy, Dimas Rizah; Kurniawan, Aditya Fahrizal; Alfani, Achmad Hafis (Indonesian Journal of Engineering and Technological Innovation, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy. However, MSMEs often face challenges in maintaining product quality due to limited machinery and suboptimal production process control, leading to losses. One example is the production of shrimp paste at UD Nurhayati, with a capacity of approximately 3 dozen cups per month. Defective products were found due to poorly controlled processing. These defects included uneven shrimp paste texture and high humidity levels that could potentially lead to mold growth. This study aimed to identify the root cause of problems in the production line using the Root Cause Analysis (RCA) method, followed by improvements through the implementation of the Plan, Do, Check, and Action (PDCA) cycle to assist UD Nurhayati in addressing defective products. Based on the results of the application of these methods, this study produced several outcomes, namely a significant reduction in the number of defective products and an increase in production capacity of 33.3% and 14.95%, respectively, compared to the condition before the improvements were made. This study indicates that the application of the PDCA and RCA methods can improve the quality and effectiveness of the production process. These results imply that UD Nurhayati needs to standardize work procedures and provide ongoing training for employees to maintain consistent product quality.